Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1108/08858629210037182
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Manufacturing Environment: Implications for Marketing

Abstract: Considers the response of US firms to the recent decline in productivity, growth etc and the subsequent adoption of just in time manufacturing pioneered by Japanese industry. Examines the concentration on the reduction in time and costs of the early stages of the product life cycle and the flexibility this allows the subsequent pricing strategies. Highlights the emphasis placed on distribution scheduling and the consolidation of transportation services. Concludes that US firms have accepted that JIT and cost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Several scholars (such as Blois, 1991;Ettlie, 1997;Clark and Fujimoto, 1991;St. John and Hall, 1991;Morris and Morris, 1992;Olson et al, 2001;Paiva, 2010;Song et al, 1997;Sawhneyand Piper, 2002;Tatikonda and Montoya-Weiss, 2001) have found that the integration between marketing and operations positively impacts several aspects of a firm, for example new product development, production planning, quality management, just-in-time implementation, advanced manufacturing implementation, on-time delivery and short lead time.…”
Section: Manufacturing Operational Capability and Market Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scholars (such as Blois, 1991;Ettlie, 1997;Clark and Fujimoto, 1991;St. John and Hall, 1991;Morris and Morris, 1992;Olson et al, 2001;Paiva, 2010;Song et al, 1997;Sawhneyand Piper, 2002;Tatikonda and Montoya-Weiss, 2001) have found that the integration between marketing and operations positively impacts several aspects of a firm, for example new product development, production planning, quality management, just-in-time implementation, advanced manufacturing implementation, on-time delivery and short lead time.…”
Section: Manufacturing Operational Capability and Market Responsivenessmentioning
confidence: 99%
“…Investigating the strategic alignment of manufacturing firms' operations, market responsiveness and performance -considered in totality -is unique (Ang et al, 2015;Jusoh, 2008;Ketokovi, 2004;Laugen, 2005;Morgan et al, 2009;Shin et al, 2015;Silveria, 2001). Several published consider manufacturing operations or market responsiveness, but little literature assesses integration of manufacturing and marketing in a coherent way (Morris and Morris, 1992;Marques et al, 2014). This study is in the Indian context, and as such provides a South Asian perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Blois, 1991;St. John and Hall, 1991;Morris and Morris, 1992;Whybark, 1994;Ghose and Mukhopadhyay, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Suppliers would become responsible for deliveries, with buyers specifying delivery date rather than ship date. Since 1982, a number of papers have been published which specifically address the sales/marketing and operations/JIT interface (Zelbst et al , 2010; Calantone et al , 2002; Hausman et al , 2002; Narasimhan and Kim, 2002; O'Leary‐Kelly and Flores, 2002; Sawhney and Piper, 2002; Singhal and Singhal, 2002; Spencer and Cox, 1994; Whybark, 1994; Ghose and Mukhopadhyay, 1993; Morris and Morris, 1992; Blois, 1991; Deane et al , 1991; Fitzsimmons et al , 1991; Gilbert et al , 1994; Roth and van der Velde, 1991; St John and Hall, 1991; Dion et al , 1990; Natarajan and Weinrauch, 1990; O'Neal, 1984, 1989) with key findings being that interdependent marketing and operations actions are superior to independent ones (Abad and Sweeney, 1982), integration of marketing and manufacturing decisions impacts organizational performance (O'Leary‐Kelly and Flores, 2002) and collaboration and coordination of the two is a strategic imperative (Hausman et al , 2002). There have even been special issues of academic journals dedicated to the interactions between JIT/operations and sales/marketing: “Linking strategy formulation in marketing and operations: empirical research,” Journal of Operations Management (Berry et al , 1991); “Manufacturing‐Sales Coordination,” International Journal of Production Economics (Whybark and Wijngaard, 1994); and “Managing the interface between marketing and operations,” Journal of Operations Management (Malhotra and Sharma, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%